2016
DOI: 10.1007/s00414-016-1406-4
|View full text |Cite
|
Sign up to set email alerts
|

New approach to age estimation of male and female adult skeletons based on the morphological characteristics of the acetabulum

Abstract: Age estimation is essential to the human identification process, both in forensic and archeological contexts. Based on the previous male-specific method of Rissech et al. (J Forensic Sci, 2006, 51:213-229), a new approach to age estimation based on the acetabulum has been described and evaluated in 611 individuals from the Lisbon Collection (Lisbon, Portugal). This paper has two main goals: (1) to revise and better define the variables of Rissech's method related to the acetabular fossa, namely, variables 5, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 54 publications
2
41
0
Order By: Relevance
“…The current results are consistent with previous research by San‐Millán et al. indicating the strong age correlation of the seven acetabular variables . Other research, however, has indicated that variables of the acetabular fossa are less strongly correlated with age than variables of the acetabular rim .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The current results are consistent with previous research by San‐Millán et al. indicating the strong age correlation of the seven acetabular variables . Other research, however, has indicated that variables of the acetabular fossa are less strongly correlated with age than variables of the acetabular rim .…”
Section: Discussionsupporting
confidence: 92%
“…It is possible that fossa variables would have correlated more strongly with age in the research of Calce and Mays if the variable descriptions had been more clearly elucidated in the original method . To this end, recent research has emended the existing descriptions of the acetabular variables , modifying Variables 5 through 7 for clarity and repeatability. Future method tests should determine whether these changes have improved the method sufficiently to reduce issues of intra‐ and inter‐observer error.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The accurate estimation of age at death in human skeletal remains is a major requirement for establishing a biological profile and for individual identification and endures as a major challenge in forensic anthropology (1)(2)(3). There are several methods available based on macroscopic observation of degenerative skeletal features (4)(5)(6)(7)(8)(9)(10)(11)(12). However, these tend to have lower reproducibility because of the subjective nature of user-observation (2,11,(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%